What passes as a rigorous case study? - Gibbert, Michael; Ruigrok, Winfried; Wicki, Barbara (Strategic Management Journal, 2008)
Abstract This article investigates the methodological sophistication of case studies as a tool for generating and testing theory by analyzing case studies published during the period 1995–2000 in 10 influential management journals. We find that case studies emphasized external validity at the expense of the two more fundamental quality measures, internal and construct validity. Comparing case studies published in the three highest‐ranking journals with the other seven, we reveal strategies that may be useful for authors wishing to conduct methodologically rigorous case study research. Copyright © 2008 John Wiley & Sons, Ltd.